Analysis of Calculating the Cost of Goods Produced by a Car Body Company Using the Activity-Based Costing Method in Determining Selling Prices (Case Study at PT. XYZ Company) - Amrih, Gilang Ganjar; Mulya, Ali Sandy (International Journal of Finance Research, 2024)
This study aims to determine the application of calculations for determining the cost of production using the Activity Based Costing method at PT. XYZ. Activity Based Costing is a method used to determine production costs per unit based on activities within the company. Data collection techniques through interviews and documentation directly to the research object. The resulting data is data related to determining the cost of production based on the ABC Costing method. The data analysis technique used is the descriptive analysis technique. This analysis is carried out by calculating the company's cost of production. Based on the research carried out, the results obtained are that in determining the cost of production using the Activity Based Costing method there are differences with the traditional method applied by the company. The differences that occur are due to the burden of overhead costs on each product. In the traditional method, overhead costs for each product are only charged to one cost driver, namely the number of units sold. In the Activity Based Costing System, overhead costs for each product are charged to several cost drivers. So that the Activity Based Costing System can allocate activity costs to each product appropriately based on the consumption of each activity and has more efficient and effective unit costs. The implementation of selling price calculations uses a burden rate so that marketing is faster in determining selling prices and can be measured to calculate production costs.